Therapeutic Applications of Ketamine in Emergency Medicine: Systematic Review - Gyawali, Suraj; Thapaliya, Rajeeb Raj; Shilpakar, Olita; Shrestha, Shreeram; Rajbhandari, Prasanna; Malla, Prajjwal; Shrestha, Bikash; Pathak, Shreeya (Grande Medical Journal, 2025)
Ketamine is a dissociative anesthetic widely used in emergency medicine due to its preservation of airway reflexes and cardiovascular stability. A systematic review of studies published between 2000 and 2024 identified 18 relevant articles evaluating ketamine use in emergency settings. Sub-dissociative doses provide effective analgesia with opioid-sparing effects, while procedural sedation, especially in children, shows high success rates. Ketamine offers hemodynamic stability during rapid sequence intubation and is effective in refractory asthma and acute agitation, often avoiding intubation. Its affordability and stability make it valuable in resource-limited settings. Ketamine remains a versatile and evidence-based option in emergency care.